Analisis Strategi Permainan dan Efektivitas Formasi dalam Futsal pada Mahasiswa - Amrizal Amrizal; Ashari Efendi; Ladipin Ladipin (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the game strategy and formation effectiveness in futsal in college students. Futsal as a fast-paced sport requires the application of the right strategy and effective formation to win. One strategy that is often used is power play, which involves the goalkeeper as an additional player to strengthen the attack. The research method used is descriptive with an observation approach and video analysis of student futsal matches. The data was analyzed to determine the strategy pattern, the type of formation used, and the success of the strategy in creating opportunities and goals. The results showed that the effectiveness of the power play strategy was still relatively low with a success rate of around 6.7%, caused by main factors such as shooting blocked by opponents, inaccurate passing, and loss of ball control. Commonly applied formations are 2-2 and 1-2-1, which provide a balance between defense and attack, but their success is highly dependent on technical ability and coordination between players. Mastery of basic techniques such as passing, control, and shooting are key in executing strategies and formations effectively. This study concludes that the development of basic technical training and improvement of team coordination are very important to improve the effectiveness of game strategies and futsal formations in university students. The adaptation of strategies according to the match situation is also a determining factor in the team's success in the competition.